The Framework for Renewing the Family System Fatwas Using the Rule of "Hardship Brings Facilitation" - Abbadi, Sona Omar Ali (Dirasat: Shari'a and Law Sciences, 2022)
Objectives: The research aims to organize the IFTA's work in a way that serves the developments related to the family system, within the rule of hardship brings facilitation since the fatwa forms a fertile ground in its applications in relation to the family system through the Fiqh and purposeful rules that revolve around the rules of lifting the embarrassment. There is a need for renewing the fatwa industry in line with reality, with an understanding of Sharia pillars and contributes to alleviating the problems and burdens of the family, lifts the embarrassment of its conditions and achieves stability, without losing the identity of Islam in its tolerant form. Methods: The researcher used the descriptive analytical approach by collecting data and information to highlight the importance of the fatwa guiding framework, and linking data and questions to find solutions to problems related to the family through the rule of "hardship brings facilitation", and extract results for applying fatwas through the Jordanian Personal Status Law. Results: The rule of "hardship brings facilitation" is one of the most prominent rules related to the application of the fatwa in the family system within its legal and economic fields, and through linking the rule with other rules to alleviate burdens, and this requires qualifying muftis in the contemporary fatwa industry, by preparing for calamities before they occur. Conclusions: Holding workshops, fatwa councils and conferences to rehabilitate the muftis, and develop their performance to keep pace with developments at all levels.